Role of Transcription Factors in Peripheral Nerve Regeneration - Patodia, Smriti; Raivich, Gennadij (Frontiers in Molecular Neuroscience, 2012)
Following axotomy, the activation of multiple intracellular signalling cascades causes the expression of a cocktail of regeneration-associated transcription factors which interact with each other and the extracellular environment to determine the fate of the injured neurons. The nerve injury response is channelled through manifold and parallel pathways, integrating diverse inputs and controlling a complex transcriptional output. Transcription factors form a vital link in the chain of regeneration, converting injury-induced stress signals into downstream protein expression via gene regulation. They can regulate the intrinsic ability of axons to grow, by controlling expression of whole cassettes of gene targets. In this review, we have investigated the functional role of a number of different transcription factors – c-jun, ATF3, CREB, STAT3, C/EBP β & δ, Oct-6, Sox11, p53, NFκB, and ELK3 – in peripheral nerve regeneration. Studies involving use of conditional mutants, microarrays, promoter region mapping and different injury paradigms, have enabled us to understand their distinct as well as overlapping roles in achieving functional and anatomical regeneration after peripheral nerve injury.